(untitled) (Research, Society and Development, 2021)
This article aims to understand the likely implications of startup accelerators in the Brazilian economy and their legal nuances in Brazilian law, measuring the impact of their activity and the ways in which they operate. The methodological approach that structures this research is a qualitative one, of bibliographic nature, with a deductive hypothetical approach, whose examination of the data took place through Discursive Textual Analysis, encompassing consultations on public information available on Brazilian programs that assist organizations in analyze. The research script begins with a conceptual study of the entrepreneurial ecosystem and startups in the light of Corporate Law; we continue with a digression about the opportunities that innovation can generate, especially in the scope of small businesses. Then, it seeks to understand the participation of the angel investor, and its legal aspects. Finally, the roles of the lawyer are examined in relation to the main challenges of the law in relation to the expansion of startups in the national scenario. Through this study it was possible to understand the impact of the presence of startup accelerators on the economy, as well as the legal solutions for the consistent development of the Brazilian entrepreneurial ecosystem.